Exosomes carry IL-10 and antigen/MHC II complexes to induce antigen-specific oral tolerance. (September 2020) - Zeng, Hao-Tao; Liu, Jiang-Qi; Zhao, Miao; Yu, Dian; Yang, Gui; Mo, Li-Hua; Liu, Zhi-Qiang; Wang, Shuai; Liu, Zhi-Gang; Yang, Ping-Chang
Abstract: Background: It is known that the immune tolerance can be naturally established in the intestine, while the mechanism by which the immune tolerance development in the intestine is not fully understood yet. Vasoactive intestinal peptides (VIP) has the immune regulatory functions. This study aims to investigate the role of VIP in the immune tolerance development in the intestine. Methods: Intestinal epithelial cell (IEC)-derived exosomes were prepared. The exosomes carried IL-10 and antigen/MHC II complexes. VIP-deficient (VIPd) mice and wild type mice were employed to test the role of VIP in the development of immune tolerance in the intestine. Results: VIPd mice failed to induce type 1 regulatory T cells (Tr1 cells) in the intestine and retarded the establishment of antigen (Ag)-specific immune tolerance. Exposure to VIP in the culture induced IL-10 expression in intestinal epithelial cells (IECs). Exosomes derived from ovalbumin (OVA, used as a specific Ag)/VIP-primed IECs carried IL-10 and OVA/MHC II complexes; these exosomes were designated IL10CARs (IL-10/chimeric antigen receptor-carrying exosomes). IL10CARs could recognize OVA-specific CD4 + T cells and converted OVA-specific CD4 ± T cells to OVA-specific Tr1 cells. Administration of IL10CARs suppressed experimental food allergy. Conclusions: The data show that IL10CARs are capable of suppressing experimental FA by inducing antigen-specific Tr1 cells, which has the translation potential for FA treatment.